1992
DOI: 10.1159/000182528
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatility of Growth Hormone Secretion and its Relation to Growth

Abstract: 84 short children were submitted to nocturnal spontaneous growth hormone (GH) secretion tests and to provocative insulin-arginine tests. Discrepancies between the GH peak under the provocative test (I-AP) and nocturnal GH maximal peak (PA) and mean concentration (MC) were frequently observed, despite significant statistical correlation between I-AP and PA (r = 0.47; p < 0.02) and between I-AP and MC (r = 0.42; p < 0.02). Night profiles were evaluated by time analysis: 31 fitted a theoretical model, consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…This result, even though obtained in a limited number of subjects, confirms the lack of relationships in humans, during exogenous GH administration, between growth velocity and pulsatility GH indices [17]. Considering that a relationship between 24-hour secretion and growth velocity has been described [11]in normal children, it seems that in humans, also when GHD, the 24-hour quantity of available GH is more important for the growth-promoting effects than GH pulsatility.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This result, even though obtained in a limited number of subjects, confirms the lack of relationships in humans, during exogenous GH administration, between growth velocity and pulsatility GH indices [17]. Considering that a relationship between 24-hour secretion and growth velocity has been described [11]in normal children, it seems that in humans, also when GHD, the 24-hour quantity of available GH is more important for the growth-promoting effects than GH pulsatility.…”
Section: Discussionsupporting
confidence: 74%
“…Considering that clear evidence of a relationship between the subcutaneous GH administration frequency and the serum IGF-I increase is lacking and that it is debated whether the rate increase in serum IGF-I is related with the growth rate (the relationship described by Mandel et al [16]has not been constantly confirmed [9, 17]), continuous subcutaneous GH administration seems to have, if any, exclusively slight metabolic effects compared with single daily injection [3], without an important effect on growth rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This GH variability is a well-described phenomenon and it is likely to be due to its pulsatile nature [21,22]. GH levels were not significantly different from baseline in the placebo group but were increased after all anamorelin doses (Fig.…”
Section: Effect On Growth Hormonementioning
confidence: 85%
“…infusion of GH are equally effective in generating a higher serum IGF-1 increase than two large i.v. boluses in GH-deficient patients [16], although no relationships have been found between IGF-I levels and growth velocity [17].…”
Section: Discussionmentioning
confidence: 99%